Pengaruh Konten Visual Estetik terhadap Minat Konsumen melalui Media Sosial Tiktok : Studi Kasus pada Konsumen Konten Minuman Estetik di Tuban - Ica Dahlia Destatiana; Zahra Azalia Rizqina; Anggiska Putri Febiyanti; Tan Evan Tandiyono (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of digital technology and social media has significantly transformed consumer behavior in the modern era. TikTok has emerged as one of the most influential social media platforms, particularly among young consumers, due to its ability to present visually appealing and engaging content. Aesthetic visual content refers to videos or images designed with attractive concepts, harmonious color combinations, proper lighting, modern editing techniques, and creative visual presentations that enhance audience engagement. This study aims to analyze the influence of aesthetic visual content on consumer interest through TikTok social media, specifically focusing on aesthetic beverage content in Tuban. The research employed a qualitative descriptive approach using observation, interviews, and documentation methods. The findings reveal that aesthetic visual content significantly affects consumer attention, curiosity, emotional attraction, and purchasing intention. Attractive visual elements encourage consumers to explore products further and increase the likelihood of purchase decisions. Moreover, TikTok contributes to the development of new digital consumption patterns in which consumers are more attracted to products with appealing visual presentations than conventional promotional methods. This study highlights the importance of visual marketing strategies in influencing consumer behavior, particularly among young digital consumers.